Narrow but underdetermined: interpretational issues considering the analysis of electoral pledges - Nieminen, Sakari; Ylisalo, Juha (Springer Science and Business Media LLC, 2025)
The study of electoral pledges has become an increasingly influential approach to parties’ programmatic commitments and their consequences. Researchers identify specific policies to which parties commit themselves in their electoral campaigns and examine whether these policies have subsequently been enacted. This approach relies on largely standardized methods and definitions, a central aim being the comparability of the results obtained in different contexts. Our article highlights methodological challenges related to the identification of pledges. Specifically, we are concerned with the narrow understanding of the concept of electoral pledge that is applied in several case studies, whereby a pledge is defined as a clear commitment to an action or an outcome whose occurrence can be verified. This operationalization appears to minimize discretion with respect to the contents of the pledges that parties have made, on one hand, and whether parties have carried out their pledges, on the other. However, this narrow understanding of electoral pledges is not as straightforward and simple as it appears. Building on the linguistic underdeterminacy thesis and using examples from a real coding process, we highlight several ways in which even this narrow operationalization leaves room for interpretation on behalf of researchers. Specifically, coders may attach differing weights to parts of a statement, concepts may have non-obvious meanings, and some words may mean different things to different audiences. We conclude that from the point of view of transparency, the field would benefit from observing the linguistic nature of electoral pledges in greater detail.